Three Preconfederation Painters of the Canadian City, Part I, James Cockburn - Caulfield, Jon (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1987)
James Cockburn, James Duncan and Joseph Légaré were the foremost painters of pre-Confederation Canadian cityscape and city life. Their work may be treated as cultural artifacts, linked to and suggesting insights about the period's social life; as aesthetic objects within the semi-autonomous realm of "art", to be treated with in the context of critical sociology; or as historical documents offering direct evidence about pre-Confederation urban physical and social landscape. The present article emphasizes the first approach, while also indicating some directions for inquiry within the second and third approaches.